The Antiobesity Effect of GLP-1 Receptor Agonists Alone or in Combination with Metformin in Overweight /Obese Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Xiaorui Lyu; Taibiao Lyu; Xue Wang; Huijuan Zhu; Hui Pan; Linjie Wang; Hongbo Yang; Fengying Gong (International Journal of Endocrinology)
Objectives. Both glucagon-like peptide-1 receptor agonists (GLP-1RAs) and metformin (MET) have markedly antiobesity effects in overweight/obese polycystic ovary syndrome (PCOS) patients. However, there was no literature to compare the antiobesity effects of these two medicines. Therefore, a systematic review and meta-analysis were conducted in our present study to evaluate the antiobesity effects of GLP-1RAs either as monotherapy or combined with MET in comparison with MET alone in overweight/obese PCOS patients. Methods. All randomized controlled trials (RCTs) which reported the efficacy of GLP-1RAs and MET in overweight/obese PCOS patients in Medline (from Pubmed), Embase, Cochrane Central Register of Controlled Trials, Web of Science, and Scopus databases were independently searched by two reviewers. The random-effect model was used to pool data extracted from the included literature. The weighted mean difference (WMD) and 95% confidence interval (CI) were used to present the meta-analysis results (PROSPERO registration number: CRD42020173199). Results. A total of eight eligible RCTs were finally enrolled in our meta-analysis from the 587 retrieved literature. The results showed that GLP-1RAs alone or combined with MET was associated with a greater weight loss (N = 318, WMD = −2.61, 95% CI: −3.51 to −1.72, P≤0.001, I2 = 77.5%), more obvious reduction of waist circumference (N = 276, WMD = −3.46, 95% CI: −4.36 to −2.56, P≤0.001, I2 = 0.0%), and body mass index (BMI) (N = 318, WMD = −0.93, 95% CI: −1.60 to −0.26, P=0.007, I2 = 84.9%) in overweight/obese PCOS patients when compared with MET alone. Further sensitivity analysis demonstrated that the meta-analysis results of the efficacy differences in terms of body weight, waist circumference, and BMI were relatively stable and reliable. Conclusion. Our meta-analysis demonstrated that the antiobesity effect of GLP-1RAs alone or combined with MET  was superior to MET  alone in terms of weight loss, the reduction of waist circumference, and BMI. More large-scale, high-quality RCTs are needed to further confirm these results in PCOS patients.